Building Reciprocal Relationships in the Student Teaching Practicum - Davis, Jacqueline; Hall, Joan Kelly (The ESPecialist, 2012)
This research study reports on the collaborative effort of university supervisors and pairs of cooperating and student teachers of Spanish. The cohort collaboratively designed experiences, responsibilities, and concessions for student teachers to facilitate the development of reciprocal relationships. The study identifies elements that enhanced or hindered reciprocity in the teaching relationship. This report emphasizes the responsibility each member of the cooperating teacher-student teacher pair has to cultivate reciprocity. It concludes with a discussion of how teacher educators can promote the success of the student teaching experience and with suggestions for future research in foreign language teacher development.